Gender, Inheritance, and the Living Qur'an: The Implementation of Justice for Women in Inheritance Distribution in Aceh, Indonesia - Mukhtar, Makmunzir; Hude, Darwis; Hidayat, Muhammad; Alfin Niam, Mohammad; Julianto, Teguh Arafah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study examines how gender justice for women is negotiated in inheritance distribution in Aceh, Indonesia, through the perspective of the Living Qur’an. It focuses on how Acehnese Muslims understand and practice Qur’anic teachings on inheritance within a strong local cultural context. The study addresses two questions: (1) how the Qur’anic inheritance verses (āyāt al-mawārīth) are understood in Acehnese society, and (2) how gender justice is realized in local inheritance practices. This research employs a qualitative design using the Living Qur’an approach. Data were collected through in-depth interviews, participant observation, and document analysis in several regions of Aceh, involving religious scholars, customary leaders, and family members with direct experience in inheritance practices. The findings reveal that inheritance distribution in Aceh is not applied through a strictly textual model but is shaped by continuous negotiation between Islamic legal principles and local customs. Mechanisms such as hibah, wasiat, hareuta peunulang, and family deliberation are used to balance Qur’anic norms with social realities and to achieve a locally accepted sense of justice for women. Rather than indicating a deviation from Islamic law, these practices demonstrate how the Qur’an operates as a living ethical framework in everyday life. This study argues that Islamic inheritance law in Aceh functions not merely as a formal legal system but as a living tradition that adapts to socio-cultural contexts while maintaining its normative foundation, thereby enabling a contextual realization of gender justice.